MODELING AND ANALYSIS OF HEAT PROCESSES IN SILICON GETEROSTRUCTURES DURING QUICK THERMAL PROCESSING - Asanov, D.J. (SCIENCE and SOCIETY, 2026)
The paper presents modeling and experimental study of thermal processes in silicon-based Ni (5 at. % Pt)/Si heterostructures under rapid photon annealing. Three heat transfer regimes are analyzed: adiabatic, heat-flow, and thermal-balance. Temperature profiles show that at an energy density of 255 J/cm2 and a pulse duration of 1.8 s, the system reaches a thermal balance mode enabling uniform heating and the formation of the Ni2Si phase. Pt-doping improves thermal stability and reduces substrate deformation.